LONG-TERM CONSEQUENCES OF MATERNAL MENTAL HEALTH FOLLOWING PREGNANCY AND CHILDBIRTH COMPLICATIONS - Toshboyeva Shohista; Allamurotova Fotima; Axtamova Nilufar Akbarjanovna (GLOBAL SCIENTIFIC RESEARCH AND INTELLECTUAL PURSUITS, 2025)
Pregnancy and childbirth complications, such as preterm birth, miscarriage, and hypertensive disorders, pose significant risks to long-term maternal mental health, leading to elevated incidences of depression, anxiety, and PTSD persisting for years postpartum. This thesis synthesizes recent evidence from systematic reviews and cohort studies to examine these enduring effects, highlighting associations with reduced sexual satisfaction, impaired quality of life, and increased healthcare utilization. Utilizing meta-analytic approaches, the analysis reveals pooled odds ratios indicating heightened vulnerability, with interventions like targeted screening proposed to mitigate outcomes. Findings underscore the need for integrated mental health support in obstetric care, demonstrating potential reductions in chronic disorders through early identification and follow-up.